Fast Flexible Bottom‐Gated Hydrogen Sensor Based on Silicon Nanomembrane. Issue 5 (8th April 2021) - Cho, Minkyu; Cho, Incheol; Kim, Kyuyoung; Park, Inkyu
Abstract: High performance flexible hydrogen sensor using a silicon nanomembrane (Si NM) coated with palladium nanoparticles (Pd NPs) is developed. After the formation of gate structure on a released Si NM, selectively pre‐doped Si NM is flip‐transferred onto a plastic substrate. Along with Pd NPs deposited on top of the Si channel, the bottom gate structure allows the sensor to operate in a sub‐threshold regime maximizing the response and recovery speed. A device simulation study revealed that the current change caused by shifting the threshold voltage upon H2 exposure is the main operating mechanism of the sensor. The fabricated sensor shows high response (up to 250% @ 0.7% H2 concentration), short response time (τ10–90 = 10 s), and short recovery time (τ90–10 = 10 s). In addition, the sensor shows low detection limit (50 ppm) and high mechanical robustness. Abstract : Palladium nanoparticle‐decorated flexible silicon nanomembrane (Si NM) hydrogen sensor demonstrates highly sensitive and fast response with bottom‐gated transistor structure. The sensor is fabricated with a transfer of pre‐doped Si NM from a rigid substrate to a plastic substrate. The sensor shows excellent performance such as high response, short response/recovery time, high gas selectivity, and mechanical robustness.